2016
DOI: 10.1093/jac/dkw456
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of fosfomycin, β-lactams and peptidoglycan recycling inhibition againstPseudomonas aeruginosa

Abstract: PG recycling inhibitors are envisaged as useful adjuvants in the treatment of P. aeruginosa infections with β-lactams and fosfomycin and therefore further development of these molecules is encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Besides aminoglycoside hypersusceptibility, the selected mutants also present fosfomycin collateral susceptibility, although the causes of this phenotype are unknown. It has been shown that mutants defective in the P. aeruginosa peptidoglycan recycling pathway show a marked increase in fosfomycin susceptibility (60). Although mutations in these elements were not found in the evolved populations, it is still possible that they might present altered levels of expression, an issue that remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Besides aminoglycoside hypersusceptibility, the selected mutants also present fosfomycin collateral susceptibility, although the causes of this phenotype are unknown. It has been shown that mutants defective in the P. aeruginosa peptidoglycan recycling pathway show a marked increase in fosfomycin susceptibility (60). Although mutations in these elements were not found in the evolved populations, it is still possible that they might present altered levels of expression, an issue that remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…There are several resistance mechanisms capable of reducing the sensitivity of fosfomycin (29). Hamou-Segarra et al evaluated P. aeruginosa mutant isolates defective in several components of the peptidoglycan recycling system exposed to fosfomycin and imipenem alone or in combination and showed that the hyperproduction of AmpC significantly increased susceptibility to fosfomycin (30). Using a hollow-fiber infection model, Drusano et al evaluated the activity of meropenem and fosfomycin against P. aeruginosa at a high inoculum (8.18 log 10 CFU/ml) and demonstrated that the combination resulted in significant synergism and was also able to contain the amplification of the subpopulation of mutants resistant to both antimicrobials; the authors speculated that the different mechanisms of action of the agents and the AmpC hyperproduction, commonly expressed in the presence of carbapenems, could be responsible for these positive effects (31).…”
Section: Discussionmentioning
confidence: 99%
“…␤-Lactams mainly act on a late stage in cell wall synthesis by preventing the transpeptidation of peptidoglycan. It is important to recognize that ampC overexpression results in a change in susceptibility to fosfomycin (11). Hamou-Segarra demonstrated this clearly (11), but it should be recognized this demonstration was with an isolate with inactivation of the three ampD amidases.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize that ampC overexpression results in a change in susceptibility to fosfomycin (11). Hamou-Segarra demonstrated this clearly (11), but it should be recognized this demonstration was with an isolate with inactivation of the three ampD amidases. Meropenem and other carbapenems are strong inducers of ampC production, and this may be another mechanism by which there is meropenem/fosfomycin synergy.…”
Section: Discussionmentioning
confidence: 99%